2007
DOI: 10.1063/1.2766835
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond cellular transfection using a nondiffracting light beam

Abstract: The ability to permeate selectively the cell membrane and introduce therapeutic agents is a key goal in cell biology. Optical transfection is a powerful methodology but requires exact focusing due to the required two-photon power density. The authors use a Bessel beam that obviates the need to locate precisely the cell membrane, permitting two-photon excitation along a line leading to cell transfection. Assuming a minimum efficiency of 20%, the Bessel beam offers transfection at axial distances 20 times greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 7 publications
0
97
0
Order By: Relevance
“…It has been shown that the Bessel beam (BB), which can be regarded as a "nondiffracting" rod of light, can be used to increase the tolerance of axial positioning and improve the transfection range [31]. It was also shown that an axicon created BB can be steered and multiplexed by a SLM [24].…”
Section: Controlled Multiple Dosementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the Bessel beam (BB), which can be regarded as a "nondiffracting" rod of light, can be used to increase the tolerance of axial positioning and improve the transfection range [31]. It was also shown that an axicon created BB can be steered and multiplexed by a SLM [24].…”
Section: Controlled Multiple Dosementioning
confidence: 99%
“…However, the usable range of high power density in a BB depends on the number of rings in the lateral intensity distribution, each of which carries an approximately equal amount of power. For example Tsampoula et al [31] used a total power of 630 mW at the sample to create a BB with approximately 70 mW in the central core with nine concentric rings around it. In a SLM system in which the power at the sample is significantly limited by the diffraction efficiency of the SLM this approach is unfeasible.…”
Section: Controlled Multiple Dosementioning
confidence: 99%
“…A number of papers (e.g., [109,110]) have since characterized the increased cell viability (about 80%), superior transfection efficiency (about 60%), and cellular volume exchanged during femtosecond optoporation. Efforts to facilitate the application of this technique are proceeding along several fronts, including nondiffracting light beams to simplify targeting of the cell membrane [111] and optical fiber-mediated transfection to simplify delivery of pulses from fiber laser systems [112]. As the technology becomes more accessible, more studies will demonstrate the efficacy of femtosecond optoporation in more applications, enabling mainstream use.…”
Section: Chromosomes and Organellesmentioning
confidence: 99%
“…In the context of optical trapping, this property has been exploited to manipulate simultaneously particles in multiple planes. 5 Recently, the propagation-invariant and self-healing properties of Bessel beams have been used to enable efficient twophoton photoporation and transfection of cells, 6 avoiding the need for the careful positioning of a small focal region. In addition, the concentric rings of light associated with the transverse intensity profile have been used to enable the static optical sorting of both silica microspheres, as a function of size 7 and human blood cells, as a function of shape.…”
mentioning
confidence: 99%